PENGARUH PEMBELAJARAN DARING MATA KULIAH MANDARIN KOMPREH ENSIF TERHADAP KEEFEKTIFAN PEMBELAJARAN MAHASISWA PRODI PBM - Rusmita, Devi; Thamrin, Lily; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to determine how effective the implementation of online learning is for students. The impact of Covid-19 has led to the implementation of online learning. Online learning has many challenges, including student"™s focus is not effective because the process of delivering material is not done directly or face to face. carried out online learning activities well. This is indicated by student statements, that lecturers can explain the material well and students easily understand it. Lecturers also make good use of technology to support online learning. In addition, students stated "strongly agree" that the lecturer had time to respond to their responses and questions. The results showed that most of the students had been able to use learning tools well to reduce the obstacles that occurred during lectures. Effectiveness becomes a guide for the success of a learning activity. These results show as many as 3.41% of students feel 'enough' with the statement. The author interprets that the informants still do not feel the benefits of the positive impact and also feel the negative impact of this online learning. The author suggests that online learning activities take place interspersed with face-to-face learning approximately one to two times a week. The author also proposes that teachers increase creativity by using learning media that can make it easier for students to understand lecture material.